Pattern of clinical presentation of bronchial carcinoma - Md Shahen; Khan, Ashraful Alam; Chisty, Md Mashukur Rahaman; Khan, Mohammad Asaduzzaman; Khan, Md Faysal; Alam, Nasrin; Nesa, Jiban (Journal of Dhaka National Medical College & Hospital, 2022)
Background: Lung cancer is most common cancer world-wide, accounting for 1.2 million new cases annually in 2000, and causing 18% of all cancer deaths. The prevalence of lung cancer is second only to prostate cancer in men and breast cancer in women. The disease caused more than 158,000 deaths-more than colorectal, breast, and prostate cancers combined. Objective: The study was carried out to evaluate the clinical presentation of bronchial carcinoma. Methods: This observational study was carried out in the Department of Medicine (Respiratory wing), Bangabandhu Sheikh Mujib Medical University (BSMMU) and National Institute of Chest Disease (NIDCH) during the period of september 2011 to February 2012. A total of 60 admitted patients with a clinical, radiological and histological diagnosis of bronchial carcinoma were enrolled in the study. Complete sociodemographic characteristics, smoking status, radiological, and histopathological characteristics of the tumor were recorded in the study. CT scan of the chest was done in the majority of the patient. CT-guided FNAC and US guided FNAC tissue sampling from lung lesions followed by histopathological examination was done to diagnose the appropriate tumor type. After collecting the data, the statistical analyses were performed using the licensed version of Statistical Package for the Social Science Version 23 (SPSS-23). Results: Out of 60 cases, majority 27 (45.0%) patients were belonged to age 51 to 60 years with mean age was 58.4±10.2 years Male: female ratio was 4.1. Three fourth (75.0%) of the patients were smoker. Cough (90.0%) was the most frequent pulmonary symptoms of bronchial carcinoma followed by dyspnoea (55.0%), wheeze (40.0%), chest pain (20.0%) and haemoptysis (15.0%). Loss of weight (90.0%) was the most frequent extra pulmonary symptoms of bronchial carcinoma followed by loss of appetite (85.0%), fever (70.0%), face & neck swelling (10.0%), horseness (5.0%) and dysphagia (5.0%). Physical findings of the patients were anaemia (35.0%), clubbing (70.0%), features of pleural effusion (50.0%), features of consolidation (25.0%), features of collapse (10.0%), palpable lymph node (10.0%) and features of SVC obstruction (10.0%). Squamous cell carcinoma (50.0%) was the most common histological pattern of bronchial carcinoma followed by adenocarcinoma (45.0%) and small cell carcinoma (5.0%). Diagnostic procedure of bronchial carcinoma was bronchoscopy & biopsy (15.0%) followed by CT guided FNAC (50.0%), US guided FNAC (5.0%), pleural biopsy (5.0%), lymph node biopsy (20.0%) and pleural fluid study (5%). Conclusion: Thus, our analysis suggests that most of the patients were elderly and males were predominant with smoking as the principal risk factor. Squamous cell carcinoma still remains the commonest histological subtype. CT guided FNAC was most detected of bronchial carcinoma. J. Dhaka National Med. Coll. Hos. 2022; 28 (02): 17-22